2023
DOI: 10.1038/s41598-023-27590-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis in myocardium of spontaneously hypertensive rats

Abstract: Hypertension-related left ventricular hypertrophy is recognized as a good predictor of adverse cardiovascular events. However, the underlying mechanism of left ventricular hypertrophy is still not fully understood. This study employed liquid chromatography coupled with tandem mass spectrometry to investigate global changes in protein profile in myocardium of spontaneously hypertensive rat, a classical animal model of essential hypertension. There were 369 differentially expressed proteins in myocardium between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Seven KEGG pathways were associated with different trait pairs. The pathways involved in drug metabolism by cytochrome p450 and the metabolism of xenobiotics by cytochrome p450 were related to the balance between the oxidative stress system and antioxidant capacity and might play a vital role in hypertension-related conditions/diseases [ 38 ]. In addition, another study found that both hypertension and high cholesterol in animal models lead to increased systemic and vascular oxidative stress, resulting in reduced vasodilatation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seven KEGG pathways were associated with different trait pairs. The pathways involved in drug metabolism by cytochrome p450 and the metabolism of xenobiotics by cytochrome p450 were related to the balance between the oxidative stress system and antioxidant capacity and might play a vital role in hypertension-related conditions/diseases [ 38 ]. In addition, another study found that both hypertension and high cholesterol in animal models lead to increased systemic and vascular oxidative stress, resulting in reduced vasodilatation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For expression analyses (C-60 Group x Hg-60 group), p < 0.05 was considered for negatively regulated proteins, and 1— p > 0.95 was considered for upregulated proteins. After compiling the results, functional analysis of the differentially expressed proteins was performed using Blas2GO 6.0 software, to determine the functional categories of proteins based on notes from the gene ontology of biological processes [ 18 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analysis was performed, according to the procedures described in previously published papers [ 9 , 18 , 19 , 20 , 30 , 31 , 32 , 33 , 34 , 35 ]. However, the statistical analysis procedures are briefly described as follows: “The images of 2D PAGE gels obtained from the renal proteome fractionation experiments (Groups C-60 and Hg-60) were analyzed with ImageMaster 2D Platinum 7.0 software (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%